Queensland Alcohol-related violence and Night Time Economy Monitoring project (QUANTEM): a study protocol - Peter G. Miller; Jason Ferris; Kerri Coomber; Renee Zahnow; Nicholas Carah; Heng Jiang; Kypros Kypri; Tanya Chikritzhs; Alan Clough; Michael Livingston; Dominique de Andrade; Robin Room; et al. (BMC Public Health, 2017)
Abstract Background Alcohol-related harm is a substantial burden on the community in Australia and internationally, particularly harm related to risky drinking practices of young people in the night-time economy. This protocol paper describes a study that will report on the changes in a wide range of health and justice outcome measures associated with major policy changes in the state of Queensland, Australia. A key element includes trading hours restrictions for licensed premises to 2 am for the state and 3 am in Safe Night Precincts (SNPs). Other measures introduced include drinks restrictions after midnight, increased patron banning measures for repeat offenders, mandatory ID scanning of patrons in late-night venues, and education campaigns. Methods The primary aim of the study is to evaluate change in the levels of harm due to these policy changes using administrative data (e.g., police, hospital, ambulance, and court data). Other study elements will investigate the impact of the Policy by measuring foot traffic volume in SNPs, using ID scanner data to quantify the volume of people entering venues and measure the effectiveness of banning notices, using patron interviews to quantify the levels of pre-drinking, intoxication and illicit drug use within night-time economy districts, and to explore the impacts of the Policy on business and live music, and costs to the community. Discussion The information gathered through this project aims to evaluate the effectiveness of the Policy and to draw on these findings to inform future prevention and enforcement approaches by policy makers, police, and venue staff.